Effects of Reclaimed Asphalt Pavement aggregates and mineral admixtures on pore structure, mechanical and durability properties of cement mortar. (20th August 2019) - Abraham, Sarah Mariam; Ransinchung R.N, G.D.
Highlights: Satisfactory performance in strength and durability by RAP mortars. Contradicting behavior of RAP mortars under sulfate attack. Cement paste was protected from frost damage in RAP mortars due to entrained air. Abstract: The study evaluate the feasibility of fine fraction of Reclaimed Asphalt Pavement (RAP) aggregates in cementitious mixes. In order to understand the true effect of fine RAP aggregates in cementitious mixes, cement mortar specimens were casted in place of concrete mixes. The natural fine aggregates were partially replaced by RAP aggregates at 25%, 50%, 75% and 100% by volume. In addition to that, cement was partially replaced by mineral admixtures like silica fume and activated sugarcane bagasse ash. The RAP inclusive cement mortars did showcase satisfactory performance in terms of strength and durability. The characteristic compressive strength and commendable flexural strength were achieved by cement mortars with RAP aggregates. Interesting results were observed for resistance against sulfate attack for RAP inclusive cement mortars where gain of strength was obtained for 25% and 50% replacement mixes even after 90 days of sulfate attack. This behavior was replicated by mineral admixture mixes with similar RAP percentage levels. The gain as well as loss in strength due to sulfate attack was substantiated using pore structure characteristics obtained by Mercury Intrusion Porosimetry (MIP). Analysis of data obtained from MIP supports the presence of entrained air in RAP mortars which suggests qualitatively that cement paste is being protected from frost damage and salt decay. This is an initial study and the same shall be replicated for concrete mixes in near future.